Role of Cytokines in experimental and clinical uveitis< - Singh Vijay; Rai Geeta; Agarwal Shyam (Indian Journal of Ophthalmology, 2001)
Uveitis is a major cause of visual impairment. Experimental autoimmune uveitis mimics the clinical conditions of posterior uveitis in many ways. T-cells (particularly CD4[+] helper-T-cells) have been shown to play an important role in pathogenesis of experimental and clinical uveitis. Based on the pattern of cytokine they secrete, CD4[+] helper cells have been divided into Thl and Th2 subsets. Various Thl and Th2 cytokines appear to be involved in the pathogenesis and/or recovery from uveitis. This article discusses in detail the uveitopathogenic and therapeutic potential of Thl and Th2 cytokines in experimental and clinical uveitis.